Gestational diabetes mellitus in sub‐Saharan Africa: systematic review and metaregression on prevalence and risk factors1. Issue 8 (10th May 2015) - Mwanri, Akwilina W.; Kinabo, Joyce; Ramaiya, Kaushik; Feskens, Edith J. M.
Abstract Objective We systematically reviewed publications on prevalence and risk factors for gestational diabetes mellitus (GDM) in the 47 countries of sub‐Saharan Africa. Methods We conducted a systematic search in PUBMED and reviewed articles published until June 2014 and searched the references of retrieved articles. We explored sources of heterogeneity among prevalence proportions with metaregression analysis. Results Of 1069 articles retrieved 22 studies were included. Half were from West Africa, specifically Nigeria, five from South Africa and six from East and Central Africa. There were differences in screening methods and diagnosis criteria used, even between studies carried out in the same country and same time period. Metaregression analysis indicated high heterogeneity among the studies (I2 = 100, P < 0.001), which could not be sufficiently explained by study setting, population, diagnostic criteria or time trend, although we observed a relatively higher prevalence in studies carried out after 2000 (5.1% vs. 3.2%), when women at risk were selected (6.5% vs. 3.8%) and when more current diagnostic criteria were used (5.1% vs. 4.2%). Associations with risk factors were reported in six studies. Significant risk factors reported in more than one study were overweight and/or obesity, family history for type 2 diabetes, previous stillbirth, previous macrosomic child and age >30 years. Conclusions There are few studies on prevalence and risk factors for GDM in Sub‐Saharan Africa and heterogeneity is high. Prevalence was up to about 14% when high‐risk women were studied. Preventive actions should be taken to reduce the short‐ and long‐term complications related to GDM in Sub‐Saharan Africa.